Analisa Data Kepuasaan Siswa Dalam Pembelajaran Online Menggunakan Metode Service Quality - Ika Ardias Nursinta; Besus Maula Sulthon (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
The student's satisfaction in this covid-19 era is crucial to figuring out what level of quality services are available in school institutions. The study aims to find out the students' level of satisfaction with online study at SMK al - amanah, this study is a descriptive quantitative study with a population of 102. In this matter student satisfaction will be measured using a servqual and importance performance analysis method in this case where it talks about dimensions of waited, responsiveness, assurance, anticipation and tangibles. The instrument of this study is done with the interview manner and the dissemination of the questionnaire. The data of the collected questionnaires are calculated and prepared, and the quality of the service is specifically known. With the spread of the questionnaire, it can be seen the result of a student's dissatisfaction with the service given. Data prepared for servqual methods with the help of SPSS 24.0 and importance performance analysis. The results from the selected student satisfaction data can be used as an evaluation material for schools to improve online learning. The results of this study show every dimension on the servqual that is tangibles, valence, responsiveness, assurance, and emphaty. Indicating that the gap or responsive gap is the biggest quality value dimension of -0.72 and the smallest gap or gap there is in realibility of -0.22